2005
DOI: 10.1007/s00114-005-0641-1
|View full text |Cite
|
Sign up to set email alerts
|

“Bicellar” Lipid Mixtures as used in Biochemical and Biophysical Studies

Abstract: Over the past decade "bicellar" lipid mixtures composed of the long-chain dimyristoyl phosphatidylcholine (DMPC) and the short-chain dihexanoyl PC (DHPC) molecules have emerged as a powerful medium for studying membrane associated, biologically relevant macromolecules and assemblies. Depending on temperature, lipid concentration and composition these lipid mixtures can assume a variety of morphologies, some of them alignable in the presence of a magnetic field. This article will examine the biophysical studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(166 citation statements)
references
References 97 publications
8
158
0
Order By: Relevance
“…4a] and ULVs at 50 8C [ Fig. 4b], are consistent with previous reports [21][22][23]. Best fits of bicelle data (i.e., at 10 8C) resulted in radii of 173, 187, and 214 Å , for [Chol]/[DMPC] = 0, 10%, and 20%, respectively, and a bilayer thickness *44 Å .…”
Section: Membrane Rigiditysupporting
confidence: 90%
See 1 more Smart Citation
“…4a] and ULVs at 50 8C [ Fig. 4b], are consistent with previous reports [21][22][23]. Best fits of bicelle data (i.e., at 10 8C) resulted in radii of 173, 187, and 214 Å , for [Chol]/[DMPC] = 0, 10%, and 20%, respectively, and a bilayer thickness *44 Å .…”
Section: Membrane Rigiditysupporting
confidence: 90%
“…Previous SANS data obtained at low temperatures (<20 8C) have indicated that the lipid mixtures in question self-aggregate into bicelles, with the long-chain lipids (e.g., DMPC, DMPG) forming the extended bilayered plane, and most of the short-chain lipid (i.e., DHPC) sequestering into the bicelle's high-curvature rim [21][22][23], as shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 83%
“…For temperatures above the gel-fluid transition, AmB slightly increased the bilayer fluidity, which was already fluid . The preferential binding of AmB to the highly disorganized edges of DODAB bicelles suggests that the same strategy could be employed for other formulations, such as mixtures of natural lipids known to form bicelles (Katsaras et al 2005).…”
Section: Detecting Dodab Bicelles By Esrmentioning
confidence: 99%
“…DMPG has the same hydrocarbon chains as those of DMPC, and is known to stabilize bicelles through electrostatic repulsion, which inhibits bicelles from fusing, as well as increasing membrane rigidity. 20 A previous report showed a non DMPG doped system ([DMPG]/[DMPC] ) 0) formed MLVs due to insufficient Coulombic repulsion between bilayers, while a highly doped system ([DMPG]/ [DMPC] ) 6.7%) formed bicelles which were unable to fuse and form ULVs at T > T c . 21 The present study focuses on the kinetics of aggregate structures that evolve from the bicelle-to-ULV transition under different temperature protocols as determined by small angle neutron scattering (SANS).…”
Section: Introductionmentioning
confidence: 99%